Unifikasi Hukum Perdata dalam Pluralitas Sistem Hukum Indonesia (Mazahib, 2014)
Plurality in Indonesiasocial order is very dominant viewed from cultural, ideological and religious aspect. It is also influential in the order of Indonesian civil law system which still undeniably plurality. State of Indonesia as a state law seeks to do the development and formation and renewal in the legal system.